2016
DOI: 10.4081/jphia.2016.515
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body fat percentage and body mass index in overweight and obese individuals in an urban african setting

Abstract: The increase in the prevalence of overweight and obesity in both developed and developing countries is associated with musculoskeletal and other non-communicable diseases. To address this, an accurate measure of body adiposity, bearing in mind several shortcomings of body mass index (BMI), should be used. This study determined the relationship between BMI and body fat (BF)% among adult Nigerians of different ethnic groups residing in an urban setting. Using multistage cluster sampling technique were recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 27 publications
(37 reference statements)
6
31
0
1
Order By: Relevance
“…Supportively, Ehrampoush et al (2016) obtained strong relationships between BIA and BMI, AVI, and WHTR in healthy adults of both genders. Similar findings were found in the studies of Akindele, et al (2016) and Ravaglia et al (1999). They found strong association between BMI and BIA in males aged over 20 years.…”
Section: Conflict Of Interestsupporting
confidence: 79%
See 1 more Smart Citation
“…Supportively, Ehrampoush et al (2016) obtained strong relationships between BIA and BMI, AVI, and WHTR in healthy adults of both genders. Similar findings were found in the studies of Akindele, et al (2016) and Ravaglia et al (1999). They found strong association between BMI and BIA in males aged over 20 years.…”
Section: Conflict Of Interestsupporting
confidence: 79%
“…Results are in line with the findings of the earlier studies that focusing on this association from the samples possessing discrete status (age, gender, or health), such as in stunted children (boys) aged 7-9 years and their mothers (Wilson et al 2011), healthy children (girls and boys) aged 3-8 years (Eisenmann et al 2004), men aged 20-95 years (Ravaglia et al 1999), obese women (Geliebter et al 2012), women with BMIs over 18.5 (Suchanek et al 2012), women aged 80 years and older (Zarzeczny et al 2016), and adult men and women (Akindele et al 2016;Ehrampoush et al 2016). They reported significant correlations between various anthropometric proxies and BIA.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Considerable recent research has focused on the association of body mass index (BMI) and bodyfat with VMS and has suggested a positive correlation between increasing BMI and the presence of VMS 24−29 . However, BMI is considered a poor predictor of body mass as it is merely a measure of excess weight and does not distinguish between body fat mass and fat free mass 30 . Our study examined the components of body composition and found lean mass, determined by both fat free mass and skeletal muscle mass, to have a significant effect on the likelihood of developing VMS over time while still considering the potential impact of fat mass.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable recent research has focused on the association of body mass index (BMI) and percent body fat with VMS and has suggested a positive correlation between increasing BMI and the presence of VMS [24][25][26][27][28][29] . However, BMI is considered a poor predictor of body mass as it is merely a measure of excess weight and does not distinguish between body fat mass and fat free mass 30 . Our study examined the components of body composition and found lean mass, determined by both fat free mass and skeletal muscle mass, to have a signi cant effect on the likelihood of developing VMS over time while still considering the potential impact of fat mass.…”
Section: Discussionmentioning
confidence: 99%